Linguistic Landscape Study on Food Court Flyers in Pamulang South Tangerang - Wirhayati; Nainggolan, Erni Susianti (Universitas Pamulang, 2025)
Linguistics landscape is a study of sociolinguistics focused on analyzing public signs in public places. This study aims to analyze multilingualism on the linguistics landscape in relation to the food court flyer in Pamulang Tangerang. This study focuses on the usage of language on the food court flyer in Pamulang Tangerang, the motive of linguistics signs used on the food court flyer, and the impression of society regarding to the linguistic signs. The research was done by capturing all linguistics signs related to food court in Pamulang South Tangerang to be analyzed in terms of its type. A flyer is a message that is put in a public place and is utilized as a very effective method of message delivery. In other words, flyer is a medium to spread certain information, advertisement, and announcement to people. It is showed that monolingual, bilingual, and multilingual signs appear on food court flyers. Moreover, mostly society views positively the usage of multilingualism on the food court flyer as it serves as intelligible, educational, and effective means. Both Indonesian and English are favorable languages to be used to attract the attention of people and consumers to the food